MAQASHID SYARIAH : DEFINISI DAN PENDAPAT PARA ULAMA - Paryadi Paryadi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The purpose of establishing law, known as maqashid al-syari'ah, is one of the important concepts in the study of Islamic law. Because of the importance of maqashid al-syari'ah, legal theorists make maqashid al-syari'ah something that must be understood by mujtahids who carry out ijtihad. The author conducted library research to explore the definitions and opinions of the scholars about maqashid al-syariah. The conclusion is that maqashid al-shari'ah is wisdom and illat is stipulated by a law. In the study of ushul fiqh, wisdom is different from illat. Illat is a certain characteristic that is clear and can be known objectively (zahir), and there is a benchmark (mundhabit), and is in accordance with legal provisions (munasib) whose existence is a determinant of the existence of law. The difference between the scholars in defining maqashid al sharia is the dynamics of ijtihad from time to time which is the breadth of Islamic sharia.